Anatomical variations of sphenoid sinus in terms of volume and protrusions of optic nerve/internal carotid artery in a subgroup of Pakistani population - Aijaz, Asma; Talat Samreen; Shazia Fehmi; Afsheen Khan; Hira Ahmed; Nadeem Baig (Journal of the Pakistan Medical Association, 2024)
Objectives: To compare the volume of sphenoid sinus with protrusions of optic nerve and internal carotid artery in both males and females. Method: The cross-sectional study was conducted from October 2020 to February 2021 at the Radiology Department of Dow University of Health Sciences, Karachi, and comprised males and females aged 20-60 years having no sphenoid sinus bony abnormality. Sphenoid volume and optic nerve and internal carotid artery protrusions were examined in the computed tomography scans of the paranasal sinus. Based on the protrusions, the scan findings were split into four groups: Group 1 had no protrusion, Group 2 had optic nerve protrusion, Group 3 had internal carotid artery protrusion, and Group 4 had protrusions of both the optic nerve and the internal carotid artery. Data was analysed using GraphPad Prism 9. Results: Of the 300 subjects, 171(57%) were males and 129(43%) were females. The overall mean age was 39.27±10.9 years. There were 147(49%) subjects in group 4, followed by 72(24%) in group 3, 42(14%) in group 2 and 39(13%) in group 1. Statistically significant difference was observed between sphenoid volume across the study groups for both male and female subjects (p<0.001). Conclusion: There was significant relationship between internal carotid artery and optic nerve protrusions and sphenoid volume. Key Words: Sphenoid sinus, Optic nerve, Internal carotid artery, Computed tomography.